2014
DOI: 10.1002/2013jd021119
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison of the cloud water phase among global climate models

Abstract: Mixed-phase clouds (clouds that consist of both cloud droplets and ice crystals) are frequently present in the Earth's atmosphere and influence the Earth's energy budget through their radiative properties, which are highly dependent on the cloud water phase. In this study, the phase partitioning of cloud water is compared among six global climate models (GCMs) and with Cloud and Aerosol Lidar with Orthogonal Polarization retrievals. It is found that the GCMs predict vastly different distributions of cloud phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
190
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(199 citation statements)
references
References 86 publications
(141 reference statements)
8
190
1
Order By: Relevance
“…As shown in Figure 3, ECHAM6-HAM2 still underestimates SLF but on average simulates twice as high SLFs as presented in Komurcu et al (2014). At -10…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…As shown in Figure 3, ECHAM6-HAM2 still underestimates SLF but on average simulates twice as high SLFs as presented in Komurcu et al (2014). At -10…”
mentioning
confidence: 64%
“…SLF has been obtained from the CALIOP satellite and has been compared to an earlier version of ECHAM6-HAM2 (Komurcu et al, 2014). At that time ECHAM6-HAM2 seriously underestimated SLF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On a global scale, the fraction of supercooled water in MPCs at various temperatures from the ECHAM6 and different versions of the CAM GCM has been compared to CALIOP satellite estimates. None of the models captured the observed variation in the supercooled fraction with temperature correctly but either simulated too small or too high values at all temperatures [46]. This is partly related to differences in INP concentrations and partly to differences in the involved parameterized microphysical processes.…”
Section: Aerosol Effects On Stratiform and Shallow Convective Mpcsmentioning
confidence: 91%
“…Recently, several studies have illustrated the importance of using a more realistic representation of cloud microphysics in climate models. For example, Cesana et al (2015) and Komurcu et al (2014) showed that climate models tend to underestimate the supercooled liquid clouds, and models that prognose separately the liquid and ice mixing ratios give a better representation of cloud properties. The RegCM version 4 (or RegCM4) regional climate model of the International Centre for Theoretical Physics (ICTP) is a widely used system that has been applied to local and regional seasonal forecasting and climate change problems for all regions of the globe (e.g.…”
Section: Introductionmentioning
confidence: 99%